METODE PENGAJIAN KITAB PADA PONDOK PESANTREN SALAFIYAH DARUL MUTTAQIN MANNANTI KABUPATEN SINJAI - Mujizatullah Mujizatullah (Al-Maraji' : Jurnal Pendidikan Bahasa Arab, 2018)
This study aims to describe the method of Pengajian Kitab Kuning that applied at the Salafiyah Darul Muttaqin Pesantren Mannanti. This research is a qualitative research. Data were collected through interviews with Kyai or leaders of Pesantren and Ustadz. The location of the study took place at the Salafiyah Darul Muttaqin Mannanti Islamic Boarding School in Sinjai Regency, South Sulawesi Province. This study found that the method applied in the Darul Muttaqin Mannanti Islamic Boarding School was (1)The Sorogan Method or the Wetonan Method, that the students proposed one of the books to study which was submitted to the ustadz to be studied by the students and translated later, after that the Ustadz listened and corrected the reading from incorrect translation of the students. (2)Method of Deliberation and discussion of Masa'il namely the method of discussion or seminar, (3)The Halaqah Method which is gathering students with teacher centred learning. (4)The memorization method is a method that is centred on memorization. The opportunity factor for the Salafiyah Darul Muttaqin Mannanti Islamic boarding school is its geographical condition which is located on the district axis road and can be reached with all types of transportation. The pesantren also has an empowerment program in the fields of agriculture, livestock and trade. As for the challenges faced, there are lacks of learning facilities and infrastructure, especially in the learning facilities which are still very simple including the female dormitory facilities which are still made of wood.Keywords: Method, Pengajian Kitab, Salafiyah Islamic Boarding School